PENILAIAN DAYA TARIK OBJEK WISATA PANTAI DI DESA TEMAJUK KECAMATAN PALOH KABUPATEN SAMBAS KALIMANTAN BARAT - Fitrian, Khairil; Husni, Harnani; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2020)
Temajuk Beach area is one of the tourism potentials that is not yet known by the wider community, which is located in Temajuk Village, Paloh District, Sambas Regency. Temajuk Beach has great potential when it is used as a tourist spot because the location of Temajuk Beach has beautiful beaches and unspoiled scenery, a lack of government contribution to make the place a tourist attraction. The purpose of the research is to find out the potential of coastal attraction at Temajuk Beach and do an assessment of the potential attractiveness of Temajuk Beach in Sambas Regency, West Kalimantan Province, especially for coastal tourism. The study was conducted in Temajuk Village, Paloh Subdistrict, Sambas District for 4 weeks. Based on the results of the study, the appraisal of attractiveness got the highest score of 1013.58 (A) assessment of clean water availability of 780 accessibility scores of 550 (C), and assessment the supporting infrastructure received a score of 720 so that it was included in the medium category (B), the assessment of the socio-economic conditions of the community got a score of 425 so that it was included in the medium category (B), while the accommodation scored the lowest value 180 and included in the category good (A). The assessment of each rating element that has been classified and then summed and gets an average total value of 611.43 from the results obtained when classified with the 2003 ODTWA PHKA development class, Temajuk Beach area gets a value (B) which means Temajuk Beach area good to be developed as a place/tourist attraction.Keyword: Potential of Coastal Ecotourism, Regency of Sambas, Temajuk Beach.